Extra-intestinal Manifestations at Diagnosis in Paediatric- and Elderly-onset Ulcerative Colitis are Associated With a More Severe Disease Outcome: A Population-based Study. (7th July 2017) - Duricova, Dana; Leroyer, Ariane; Savoye, Guillaume; Sarter, Hélène; Pariente, Benjamin; Aoucheta, Djamila; Armengol-Debeir, Laura; Ley, Delphine; Turck, Dominique; Peyrin-Biroulet, Laurent; Gower-Rousseau, Corinne; Fumery, Mathurin; et al.
Abstract: Background and Aims: Data on extra-intestinal manifestations [EIM] and their impact on the disease course of ulcerative colitis [UC] in population-based cohorts are scarce, particularly in paediatric- and elderly-onset UC patients. The aims of this population-based study were to assess: 1] the occurrence of EIM in paediatric- and elderly-onset UC; 2] the factors associated with EIM; and 3] their impact on long-term disease outcome. Methods: Paediatric-onset [< 17 years at diagnosis] and elderly-onset UC patients [> 60 years at diagnosis] from a French prospective population-based registry [EPIMAD] were included. Data on EIM and other clinical factors at diagnosis and at maximal follow-up were collected. Results: In all, 158 paediatric- and 470 elderly-onset patients were included [median age at diagnosis 14.5 and 68.8 years, median follow-up 11.2 and 6.2 years, respectively]. EIM occurred in 8.9% of childhood- and 3% of elderly-onset patients at diagnosis and in 16.7% and 2.2% of individuals during follow-up [ p < 0.01], respectively. The most frequent EIM was joint involvement [15.8% of paediatric onset and 2.6% of elderly-onset]. Presence of EIM at diagnosis was associated with more severe disease course [need for immunosuppressants or biologic therapy or colectomy] in both paediatric- and elderly-onset UC (hazard ratio [HR] = 2.0, 95% confidence interval [CI]: 1.0–4.2; and HR = 2.8, 0.9–7.9, respectively). Extensive colitis was another independent risk factor in both age groups. Conclusions: Elderly-onset UC patients had lower risk of EIM either at diagnosis or during follow-up than paediatric-onset individuals. EIM at diagnosis predicted more severe disease outcome, including need for immunosuppressive or biologic therapy or surgery, in both paediatric- and elderly-onset UC.